Case Settlement Model in Kubu Rokan Hilir District - Dasrol, Dasrol; HZ, Evi Deliana (Halu Oleo University, 2022)
Kubu Regency is one of the areas in Riau Province that still applies the settlement of legal cases using customary law, which involves the role of Ninik Mamak and traditional leaders, especially as mediators. This study aimed to know the position of Ninik Mamak and conventional leaders in every sub-district or village in Kubu District, Rokan Hilir Regency. Problem-solving involves local indigenous community leaders. The results of this study are expected to provide a solution for law enforcement officers in overcoming the many cases that cannot be resolved by the judiciary and the problem of overcapacity of correctional institutions throughout Indonesia.